Mirzā ʻAli-Qoli Khoʼi : the master illustrator of Persian lithographed books in the Qajar period. - Marzolph, Ulrich; Zenhari, Roxana (Islamic manuscripts and books, 2022)
"Mirzā 'Ali-Qoli Kho'i is the unsurpassed master of the art of illustration in Persian lithographed books of the Qajar period, both in terms of quality and quantity of production. In the decade of documented activity, 1263-72/1846-55, the artist produced more than 2,300 single images in about 70 books, plus hundreds of minutely executed small images on the margins of several books and numerous illuminated chapter headings. Prepared by Ulrich Marzolph together with Roxana Zenhari, the present publication is a comprehensive assessment of the artist's work and the first ever detailed discussion of an Iranian artist of the Qajar period. In addition, the book also serves as an introduction to Persian and Islamic art"--